Position of the Deed of Grant Whose Object Violates the Absolute Rights (Legitieme Portie) of the Heirs - Fatsya Gita Subagia; Tjempaka Tjempaka (Journal of Social Research, 2023)
A living person may give away their property by grant or gift instead of distributing it to their heirs through inheritance. When both the grantor and grantee are still alive, a grant is a legal action that aims to transfer ownership rights that are knowingly transferred to another party. Grants may be made to whoever the grantor chooses, but it must be stated that the grant's terms cannot be harmful to other people. The Burgerlijk Wetboek, or Civil Code, governs these issues. By being careful not to violate the legitimate component (absolute part). Problems with legal protection and legal repercussions for heirs about grants that hurt the absolute portion (Legitieme Portie) of the heirs will occur if they breach the law's restrictions. By looking into secondary data or library resources, the normative juridical research methodology was applied to create this paper. As a result of identifying the absolute portion (Legitieme Portie), as specified in Article 913 of the Civil Code, various provisions in the Civil Code (Burgerlijk Wetboek) have given the heirs legal protection. Then, if the heirs feel wronged by the grant or grant or based on a will or who has passed away, the legal implications of a grant deed that breaches Legitieme Portie be revoked.